Total Knee Replacement in Alkaptonuric Ochronosis : Two Case Reports and Literature Review - Pesciallo, Cesar; Garabano, German; Rodriguez, Joaquin; Viale, German; Tillet, Fernando; Del Sel, Hernan (Acta Biomedica Atenei Parmensis, 2022)
Background and objective: Alkaptonuria is a rare disease characterized by the accumulation of homogentisic acid (HGA). Over time, these patients may develop disabling ochronotic arthropathy. We present 2 cases of patients with end-stage arthropathy treated with total knee arthroplasty (TKA).Methods:  Both patients complained of disabling knee pain and reported limited walking distance (200-300 m). One had a history of osteotomy for medial knee arthtritis and ignored his underlying condition. The other presented with valgus gonoarthrosis and diagnosis of alkaptonuria.Results: Intraoperatively, the characteristic dark-blue color in the joint was observed. Both patients evolved favorably after TKA with excellent results according to the Knee Society Scores (KSS) at three years of follow-up.Conclusion: We believe TKA is the right treatment for patients with end-stage disease because it offers considerable relief from pain and allows patients to recover function.